Characterisation and treatability of natural organic matter in groundwaters used for drinking water - Hamilton, Stacey Renee (Curtin University, 2014)
Natural organic matter contributes to various potable water issues and is present in relatively high concentrations in Western Australian water supplies. Characterising natural organic matter is important for treatment of these waters, and this Thesis contributes to the body of characterisation studies providing a detailed understanding of the origins, structural features and reactivity of natural organic matter, along with its behaviour in drinking water treatment processes, allowing improved catchment management practices and optimisation of treatment processes.